Human and natural resource exposure to extreme drought at 1.0 °C–4.0 °C warming levels. (1st June 2022) - Runde, Isabelle; Zobel, Zachary; Schwalm, Christopher
Abstract: Extreme drought occurs on every continent, negatively impacting natural systems and the built environment. Realized and anticipated future warming affects global hydrology, influencing the severity and frequency of both extreme precipitation events and precipitation deficits. Understanding future drought conditions is essential for risk aware water management strategies and to protect food security for a growing human population, while safeguarding natural capital critical to limiting further warming. Here we quantify socioeconomic and ecological exposure to extreme drought. We focus on global, regional, and national scales at increasing levels of climate warming, from today's 1.0 °C world to 4.0 °C of warming. Drought is quantified using the self-calibrated Palmer drought severity index calculated from globally mosaiced regional climate simulation (REMO2015). Exposure to extreme drought increases monotonically with warming level. For every 0.5 °C warming increase up to 3.0 °C, an additional 619 million people live in areas with 25% likelihood of annual extreme drought, in addition to the 1.7 billion people (25% of 2020 global population) exposed in today's 1.0 °C world. Spatially, global drying is amplified in the tropics, where drought frequency increases at twice the global rate. Per 0.5 °C increase in warming, extreme drought annual likelihoods increase 1.5 times greater in forested than non-forested areas, jeopardizing climate regulation associated with forested biomes. Cropland exposure to 50% likelihood of annual extreme drought in two of the highest producing countries, China and Brazil, increases 4× and 13× between 1.0 °C and 2.0 °C, spanning a third of national cropland by 3.0 °C. At 1.5 °C (4.0 °C), 16% (39%) of global hydroelectric generating capacity will be exposed to at least a 50% likelihood of annual extreme drought, up from 5% in today's 1.0 °C world. Given the near-term likelihood of surpassing 1.5 °C, high resolution drought exposure assessments must inform risk aware development and resilience efforts.